Rhodotorula glutinis as a living cell liposome to deliver polypeptide drugs in vivo - Zhengbin Fei; Shiyu Li; Jiajia Wang; Yuzhe Wang; Zhenyou Jiang; Wenhua Huang; Hanxiao Sun (Taylor & Francis Group, 2019)
The potential advantages of recombinant microbes as oral drug carriers for curing diseases have attracted much attention. The use of recombinant oil microbes as living cell liposomes to carry polypeptide drugs may be an ideal polypeptide oral drug delivery system. GM4-ΔTS was constructed by LFH-PCR from Rhodotorula glutinis GM4, which was screened and preserved in our laboratory, and then transferred into choline-phosphate cytidylyltransferase (CCT), which is a rate-limiting enzyme for lecithin synthesis. The results showed that the CCT gene was highly expressed in the GM4-ΔTS strain and could significantly increase fatty acid and lecithin contents in GM4-ΔTS-PGK1-CCT. Moreover, insulin, H22-LP, and α-MSH were successfully introduced into cells in vitro, and the strain no longer proliferated in vivo, for safe and controllable polypeptide drug delivery. In vivo, normal mice were intragastrically administered with recombinant strains carrying insulin and α-MSH, and different levels of polypeptide drugs were detected in serum and tissue, respectively. Then, recombinant strains carrying insulin were administered to type II diabetes mellitus mice. The results showed that the strains could effectively reduce blood glucose levels in mice, which indicated that the recombinant strains could carry insulin into the body, and the drug effect was remarkable. Therefore, recombinant GM4-ΔTS-PGK1-CCT strains were successfully used as living cell liposomes to carry insulin, H22-LP, and α-MSH peptides into the body for the first time; additionally, these strains have enhanced safety, controllability, and efficacy.